6 x 9 / 2 = 27
Get rid of the 9. 2 times 2 times 6 equals 24.
3*6=18 18/9=2 2
6*10^9 / 2*10^3 = (6/2) * 10^9 / 10^2 = 3*10^(9-3) = 3*10^6 or 3 million.
2/3 * 9 = 6
6 x 9 / 2 = 27
6*9+2=54+2=56.
108
Get rid of the 9. 2 times 2 times 6 equals 24.
3 * 6 / 9 = 18 / 9 = 2
6+9/5-2*6 = -4.2
3*6=18 18/9=2 2
6*10^9 / 2*10^3 = (6/2) * 10^9 / 10^2 = 3*10^(9-3) = 3*10^6 or 3 million.
2/3 * 9 = 6
9 multiplied by 2/3 is 6
Ask yourself what goes in 6 and 9 evenly. the answer is 3, 3 goes into 6 Two times, and into 9 three times. Your answer then is 2 over 3, or 2/3. =)
6 ÷ 2 x 3 =9